Wobbling mass influence on impact ground reaction forces: A simulation model sensitivity analysis - Pain, M. T. G.; Challis, J. H. (Journal of Applied Biomechanics, 2004)
Wobbling mass models have been used to gain insight into joint loading during impacts. This study investigated the sensitivity of a wobbling mass model of landing from a drop to the model`s parameters. A 2-D wobbling mass model was developed. Three rigid linked segments designed to represent the skeleton each had a second mass attached to them, via two translational nonlinear spring dampers, representing the soft tissue. Model parameters were systematically varied one at a time and the effect this had on the peak vertical ground reaction force and segment kinematics was examined. Model output showed low sensitivity to most model parameters but was sensitive to the timing of joint torque initiation. Varying the heel pad stiffness in the range of stiffness values reported in the literature had the largest influence on peak vertical ground reaction force. The analysis indicated that the more proximal body segments had a lower influence on peak vertical ground reaction force per unit mass than the segments nearer the contact point. Model simulations were relatively insensitive to variations in the properties of the connection between wobbling masses and the skeleton. If the goal is to examine the effects of wobbling mass on the system, this insensitivity is an advantage, with the proviso that estimates for the other model parameters and joint torque activation timings lie in a realistic range. If precise knowledge about the motion of the wobbling mass is of interest, however, this calls for more experimental work to precisely determine these model parameters.